Comparison Between a Resistance Training and a Combined Functional and Dynamic Balance Training on Functional Fitness Performance in Older Adults (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The biological ageing process is linked to the decline in both structure and function across various physiological systems. These age-related changes can adversely affect daily activities and increase the fall risk in older adults. The aim of this study is to compare the effects of two different training protocols on functional fitness in adults over 65.Methods: Sixty older adults (76.6% women), participating in the “Promotion of Physical Activity and Prevention of Household Accidents (PAP & DAP)” project, were randomly recruited and assigned to Resistance Group (RG; n = 29; 70.8 ± 6.54 years; 66.5 ± 10.96 kg weight; 159.7 ± 7.12 cm height; 25 ± 5.78 kg/m2 body mass index) and combined Functional and Balance Group (FBG; n = 31; 72.2 ± 5.19 years; 68.5 ± 11.58 kg weight; 159.8 ± 7.51 cm height; 26.8 ± 3.89 kg/m2 body mass index). RG and FBG respectively performed resistance training with elastic bands and combined functional and dynamic balance training twice a week (4 hours) for six weeks. Functional fitness was evaluated with the Senior Fitness Test (SFT) battery, which assesses leg strength and endurance (Chair Stand Test), arm strength (Arm Curl Test), back muscle flexibility (Sit and Reach Test), dynamic balance and walking ability (Timed Up and Go Test), and aerobic endurance (Two-Minute Step Test). Data normality was assessed with the Shapiro–Wilk test. According to data distribution, intra-group differences were analysed with the Student’s paired samples t-test or the Wilcoxon test, while differences between groups with the independent samples t-test or the Mann–Whitney U test. Statistical significance was set at p